Signifier, signified, saliencing : the sign lived as an action (Signifiances (Signifying), 2019)
We situate our approach in the paradigm of enaction (Varela et al., 1991) which postulates that all cognition operates through movement in a context of body-environment interactions. The aim of this article is to rethink Saussure's sign theory (1916/1996), presented as disembodied and decontextualized, in the light of this recent paradigm, following Bottineau (2012a, b, c, d; 2017A, b, c). For this we use the Theory of Submorphemic Saliencing (Grégoire, 2012a, 2014; 2015; 2017a, b, c, d) which postulates that the enaction of meaning in discourse is based on a simplex (Berthoz 2009) and vicariant (Berthoz 2013) behavior of biocultural actions saliencing. We will first propose a terminology for distinguishing between first-order linguistic actions and second-order linguistic units, which appears fundamental for any approach to the saussurean notions of sign, signifier and signified.